Validly published but illegitimate. Correction to and comments on Phytotaxa 373: On Hemionitis atreyu, an invalid and unnecessary name, and on the correct name for that species if placed in Hemionitis (Pteridaceae subfam. Cheilanthoideae) - Mosyakin, Sergei L. (Phytotaxa, 2019)
An interesting nomenclatural case of Hemionitis atreyu Christenhusz (in Christenhusz et al. 2018: 10) was recently considered and discussed in an earlier issue of Phytotaxa (Mosyakin 2018). That species-rank name was originally proposed as a replacement name (not as a new combination with the earliest available species epithet “acrostica”) because of the existence of a supposedly earlier name, “Hemionitis acrosticha” Noronha (1790: 18; 1827: 78). However, the latter name has never been validly published (see Mosyakin 2018), and thus, if the species earlier known mainly as Cheilanthes acrostica (Balbis 1801: 98) Todaro (1866: 215) or Pteris acrostica Balbis (1801: 98) is placed in Hemionitis Linnaeus (1753: 1077), not a replacement name but a new combination was required. That combination has been validated as Hemionitis acrostica (Balb.) Mosyakin (2018: 165).